Critical Analysis of the Controversial Articles of the New Criminal Procedure Code: Threats to Human Rights Principles and Law Enforcement Accountability - Ingka Harsani Nasution; R. Panji Amiarsa; Suci Hati Handayani (Ann Publisher, 2025)
Background. The revision of the Criminal Procedure Code (KUHAP) contained in Law Number 1 of 2023 has brought significant changes to the Indonesian criminal justice system. However, several articles in the new Criminal Code have attracted controversy because they are seen as potentially threatening human rights principles and weakening law enforcement accountability. Purpose. This article critically analyzes the controversial articles in the new Criminal Code, particularly those related to the authority to arrest, detain, wiretap, and protect law enforcement. Method. Through a normative and comparative juridical approach, this study finds that several provisions in the new Criminal Procedure Code have the potential to violate the principles of due process of law, presumption of innocence, and the right to fair trial guaranteed in the constitution and international legal instruments. Conclusion. This article recommends the need for strict oversight in the implementation of the new Criminal Procedure Code, as well as revisions to problematic articles to ensure a balance between the effectiveness of law enforcement and the protection of human rights.